Gap solitons in a spin-orbit-coupled bose-einstein condensate - Kartashov, Yaroslav V.; Konotop, Vladimir V.; Abdullaev, Fatkhulla Kh. [UNESP] (American Physical Society (APS), 2013)
We report a diversity of stable gap solitons in a spin-orbit-coupled Bose-Einstein condensate subject to a spatially periodic Zeeman field. It is shown that the solitons can be classified by the main physical symmetries they obey, i.e., symmetries with respect to parity (P), time (T), and internal degree of freedom, i.e., spin (C), inversions. The conventional gap and gap-stripe solitons are obtained in lattices with different parameters. It is shown that solitons of the same type but obeying different symmetries can exist in the same lattice at different spatial locations. PT and CPT symmetric solitons have antiferromagnetic structure and are characterized, respectively, by nonzero and zero total magnetizations. © 2013 American Physical Society.
Keywords: Antiferromagnetic structures; Bose-Einstein condensates; Degree of freedom; Gap soliton; Spatial location; Total magnetization; Zeeman fields; Bose-Einstein condensation; Degrees of freedom (mechanics); Solitons